Comparison of X-Ray Absorption in Mandibular Tissues and Tissue-Equivalent Polymeric Materials Using PHITS Monte Carlo Simulations - Yasemin Gokcekuyu; Fatih Ekinci; Arda Buyuksungur; Mehmet Serdar Guzel; Koray Acici; Tunc Asuroglu (Applied Sciences)
This study investigates the absorption of X-rays in mandibular tissues by comparing real tissues with tissue-equivalent materials using the PHITS Monte Carlo simulation program. The simulation was conducted over a range of X-ray photon energies from 50 to 100 keV, with increments of 5 keV, to evaluate the dose absorbed by different tissues. Real tissues, such as the skin, parotid gland, and masseter muscle, were compared with their tissue-equivalent polymeric materials, including PMMA, Parylene N, and Teflon. The results showed that the real tissues generally absorbed more X-rays than their corresponding equivalents, especially at lower energy levels. For instance, at 50 keV, differences in the absorbed doses reached up to 50% for the masseter muscle and its equivalent, while this gap narrowed at higher energies. The study highlights the limitations of current tissue-equivalent materials in accurately simulating real tissue behavior, particularly in low-energy X-ray applications. These discrepancies suggest that utilizing tissue-equivalent materials may lead to less accurate medical imaging and radiotherapy dose calculations. Future research should focus on improving tissue-equivalent materials and validating simulation results with experimental data to ensure more reliable dosimetric outcomes. This study provides a foundation for refining radiation dose calculations and improving patient safety in clinical applications involving X-rays.